2014
DOI: 10.1080/09575146.2014.982903
|View full text |Cite
|
Sign up to set email alerts
|

Editorial

Abstract: In our call for papers for this special issue on transitions in the early years, we highlighted the issue of respectful, reciprocal relationships and the importance of listening to communities whose voices had not been previously heard. The papers published here provide an opportunity to consider these issues through new lenses, providing perspectives which include different sectors of early education; geograph- ical variations across urban, rural and remote communities; children's experiences across age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Transition to school research has largely been conducted in America (Rosenkoetter & Rosenkoetter, 1983), the UK (Katz, 2010;Fabian & Dunlop, 2007;Peters & Dunlop, 2014) and Australia (Dockett & Perry, 2004). Britto & Limlingan (2012) stress the importance of conducting research on starting school cross-culturally in their publication for UNICEF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transition to school research has largely been conducted in America (Rosenkoetter & Rosenkoetter, 1983), the UK (Katz, 2010;Fabian & Dunlop, 2007;Peters & Dunlop, 2014) and Australia (Dockett & Perry, 2004). Britto & Limlingan (2012) stress the importance of conducting research on starting school cross-culturally in their publication for UNICEF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Hayes (2013), perception is an important factor influencing early educational practices. In his study on perspectives of preschool teachers in Australia, Peters (2002) found that teachers perceived social competence skills as the most important factor for the development of practical skills related to independence, self-help, ability to listen, ability to read, sit still as well as taking turns; which have a positive link with reading skills acquisition. Gresham, Elliott, and Black (1987) contend that the type of social competence skills perceived by teachers as critical for the pupil's academic success has implications for their selection of skills to teach.…”
Section: Introductionmentioning
confidence: 99%
“…Transition to school research has largely been conducted in America (Rosenkoetter & Rosenkoetter, 1983), the UK (Katz, 2010;Peters & Dunlop, 2014) and Australia (Dockett & Perry, 2004). Britto & Limlingan (2012)…”
mentioning
confidence: 99%